Organizational Culture Change in Public Sector Development through Innovative Organizational Practices: Perubahan Budaya Organisasi dalam Pengembangan Sektor Publik melalui Praktik Organisasi yang Inovatif - Habil Seulalae, Anggos; Frinaldi, Aldri; Putra Tri Rezeki, Angga (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This article examines the role of organizational culture in public sector development through innovative organizational practices. The public sector is increasingly required to improve performance, accountability, and service quality amid complex governance challenges. Organizational culture is widely recognized as a critical internal factor influencing organizational behavior and performance; however, it is often treated as a static supporting variable rather than a dynamic process of change. This study employs a qualitative approach using a critical literature review to analyze scholarly publications published between 2021 and 2025. The literature was sourced from national and international journals through databases such as Google Scholar, Scopus, and accredited SINTA journals. The analysis was conducted using a critical thematic approach to identify dominant themes, conceptual patterns, and limitations in existing studies. The findings indicate that organizational culture plays a significant role in shaping public sector performance, adaptability, and innovation capacity. Nevertheless, most studies have not fully integrated organizational culture as an embedded and transformative process linked to innovative organizational practices. This article highlights the need for a more holistic analytical framework that connects cultural change with sustainable innovation to support long-term public sector development.